Power Generation for Wearable Electronics: Designing Electrochemical Storage on Fabrics - Ramandeep Vilkhu; Wesley Joo-Chen Thio; Piya Das Ghatak; Chandan K. Sen; Anne C. Co; Asimina Kiourti (IEEE Access, 2018)
We report a new class of textiles with electrochemical functions which, when moistened by a conductive liquid (saline solution, sweat, and wound fluid), generate dc voltage and current levels capable of powering wearable electronics on the go. Contrary to previously reported power generation techniques, the proposed fabrics are fully flexible, feel and behave like regular clothing, do not include any rigid components, and provide dc power via moistening by readily available liquids. Our approach entails printed battery cells that are composed of silver and zinc electrodes deposited onto a polyester fabric to generate power in the microwatt range. Electrochemical characterization of the discharge of a single printed battery cell in a 10 M sodium hydroxide (NaOH) electrolyte shows reproducible results with a sustained power level of ~80 μW for over 3 h. Scalable dc power may also be achieved by connecting multiple battery cells in series via flexible and conductive E-threads. Indeed, a series connection of two battery cells is demonstrated to boost the generated voltage from 1.4 to 2.5 V. Notably, this in-series printed battery arrangement is shown to successfully power a digital thermometer under 10 M NaOH, a 0.5 M sodium chloride solution (mimicking human sweat), and Dulbecco's phosphate-buffered saline solution (mimicking bodily fluid electrolytes). Overall, the proposed technology is expected to be of utmost significance for healthcare, sports, military, and consumer applications, among others.